Research progress of quality evaluation technology in black tea fermentation process - XIA Chang-yi; RAN Qian-song; LI Rui; LIU Ya-bing (Shipin yu jixie)
Fermentation is the key to the formation of characteristics and quality of black tea. It is very important to evaluate the fermentability of black tea quickly and accurately. In this paper, the application of artificial sensory evaluation technology, biochemical component detection technology, intelligent biomimetic technology, data fusion technology and intelligent biomimetic equipment in the evaluation of black tea fermentation quality in recent years was reviewed, and the development trend of intelligent biomimetic technology in the evaluation of black tea fermentation in the future was prospected.